Analisis Minat Belajar Siswa SMP Dengan Menggunakan VBA Excel Pada Materi KPK dan FPB - Yeti Jumiati; Arpin Chronika Saida Manalu; Siti Chotimah (Departement of Mathematics Education, 2019)
This study was conducted to analyze the learning interest of class VII Junior High School students in mathematics learning KPK and FPB byusing indicators of learning interest namely feeling happy, student interest, study involvement, diligent in learning and doing mathematical assignmens, diligent and learning discipline in learning. Research methods for analysis using descriptive qualitative methods, with the instrument used ini the form of quaestionnaires containing positive and negative statements to analyze student’s interest inlearning mathematics. Sampel subjects in the study were seventh grade SMP IT Daarul Fikri Bandung totaling 22 people. The result obtained from the study that the interest in learning mathematics assisted by VBA Excl on the material of KPK and FPB is good.